STRATEGI KOMUNIKASI PT. BANK RIAU KEPRI SYARIAH CABANG PEMBANTU PETAPAHAN DALAM MENSOSIALISASIKAN PERUBAHAN BANK UMUM KONVESIONAL KE BANK UMUM SYARIAH - Moehammad Afrinaldi Saputera Saputera; Ringgo Eldapi Yozani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT In 2022 PT Bank Pembangunan Daerah Riau Kepri successfully converted to BRK Syariah. Due to the lack of understanding of sharia banking among customers and prospective customers at the Petapahan sub-branch, PT. Bank Riau Kepri Syariah Petapahan Sub-Branch took steps, namely by conducting door to door outreach which was carried out from Monday – Friday every day. This research aims to find out how BRK Syariah Petapahan's communication strategy is in socializing changes from conventional commercial banks to sharia commercial banks. This study uses qualitative research methods with the presentation of descriptive analysis by describing the subject and research object based on the facts that appear. The research location chosen by the author is on Jl. Raya Petapahan, Tapung Kampang, Petapahan, Kec, Tapung, Kampar Regency. Data collection techniques in the form of observation, interviews, documentation. For the technique of checking the validity of the data using triangulation. The results of this study are the strategy for selecting communicators for all employees of the Riau Kepri Syariah bank, Petapahan sub-branch. The strategy for processing communication messages carried out by Bank Riau Kepri Syariah, Petapahan sub-branch, has several core message points, the first is related to the conversion carried out, the second is the concept of Islamic banking, the third is the contract used in Islamic banking, and the last is about Islamic products. The media selection strategy used by Instagram and WhatsApp. The strategy for determining the target of communication is for all the people of Petapahan, civil servants and private employees, DIKPORA and DINKES to work together so that the information provided is wider. Keywords : Communications Strategy, PT.Bank Riau Kepri Syariah, Socialization, Conventional Commercial Banks, Sharia Commercial Bank